DIGITALIZATION OF MSMES: UTILIZING SOCIAL MEDIA AS A MARKETING TOOL - Asnimar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Digital transformation has positioned social media as a central instrument in the development of modern business. This study employs a Systematic Literature Review (SLR) to examine the role of social media in supporting digital business strategies. The literature selection process was conducted through international databases with inclusion criteria focusing on publications from the last five years. The findings reveal that social media contributes to enhancing brand awareness, strengthening customer engagement, and creating a social commerce ecosystem that enables direct transactions. Furthermore, the use of social media analytics provides competitive advantages through market trend prediction and service personalization. Key challenges involve privacy issues, digital literacy gaps, and regulatory frameworks that have not been fully adapted. The study concludes that the success of digital business is largely determined by the ability of entrepreneurs to integrate social media innovations with sustainable risk management. These insights offer both conceptual foundations for future research and practical guidance for businesses aiming for sustainability in the digital era.